SEMIOTIC ANALYSIS OF PDI-PERJUANGAN POLITICAL CAMPAIGN ADVERTISEMENT “TUMPENG SEBAGAI KEDAULATAN PANGAN” - KARTONO, JINO PRAYUDI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : semiotics, sign, advertisement, television, pdi-perjuangan Advertisement becomes a device to promote their product, vision, and even ideology. General Election was held on 9 April 2014 and General Election for electing president was held 9 July 2014 (KPU, 2014). In this research, the researcher analyzes the sign of PDI-Perjuangan entitled “Tumpeng Sebagai Kedaulatan Rakyat”. The researcher would like to answer two problems of the study; what are the signs found in PDI-P TV political campaign advertisement and what is the meaning of signs found in PDI-P TV political campaign advertisement. The purposes of this study are to find out the signs and the meaning of the signs found in PDI-P TV political campaign advertisement. Thisstudy uses triadic taxonomy of Peirce (1958) to analyze and find the signs.This study uses qualitative research. The data of this study are taken from the advertisement of PDI-Perjuangan entitled “Tumpeng Sebagai Kedaulatan Pangan”. PDI-Perjuangan is one of political parties which compete in General Election on 9th April 2014. In this study, the researcher chooses the advertisement because there are many kinds of element of sign in this advertisement. The researcher picks the data on Youtube because this website is trusted and protected.The finding shows that based on the triadic concept of sign by Peirce (1931-1958). There are 96 signs found in this advertisement. In this advertisement, there are 59 symbols, 34  icons,and 3 indexes. Symbols is the highest numbers in one of three kinds of signs. From this finding, most of symbols are texts in this advertisement. All of the signs prove that this advertisement uses symbol as the sign to inform the viewer about the advertisement.The advertisement is found the symbol, icon, and index together and the people can know the goal of this advertisement. Most signs found are symbols. Most symbols found in this advertisement are text.